The Influence of Incentives on Employee Performance at the Bukit Layang Village Office, Sub-District Kembang Janggut Kutai Kartanegara District - Inriany Novica Ruminding; Dini Zulfiani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of incentives on employee performance at the Bukit Layang village office, Kembang Janggut District, Kutai Kartanegara Regency. This study uses quantitative research methods. The population in this study were all employees of the Bukit Layang Village Office, Kembang Janggut District, totaling 42 people. The sampling technique used in this study was saturated sampling. The saturated sampling technique was used in this study because the population was relatively small, namely 42 people, making it possible to involve all members of the population as research samples. All research participants amounted to 42 people and were used as saturated samples, with the collected population and saturated samples consisting of Bukit Layang Village Office officers. The variables studied in this study consisted of the independent variable (X) Incentives and the dependent variable (Y) Employee Performance. Employee performance can be measured through several indicators which include quality, quantity, timeliness, effective use of resources, independence, and commitment. These indicators play an important role in determining the quality and quantity of employee performance in the company. Performance appraisal at the Bukit Layang Village Office, Kembang Janggut District, is carried out in various ways based on the role of each employee in the village office. Incentives given to employees lead to financial and non-financial incentives which are assessed by looking at predetermined aspects of employee performance. The results of this study indicate that the percentage effect of incentives on employee performance at the Bukit Layang Village Office is 15.30% while the remaining 84.70% is influenced by other variables outside this study.